Twisting and bending photo-excited phenylethynylbenzenes: a theoretical analysis - Hodecker, Manuel; Bunz, Uwe H. F.; Dreuw, Andreas (Physical chemistry, chemical physics, 2020)
Oligo(phenylethynyl)benzenes are a family of compounds that exhibit a rich photochemistry changing dramatically with different orientation of a phenyl group in the molecule. Quantum-chemical calculations have been performed to investigate different members of this family of compounds and compared to previous experimental and theoretical studies. 1,4-Bis(phenylethynyl)benzene (BPEB) has different optical properties than its smaller relative diphenylacetylene; however, upon twisting an outer phenyl ring of BPEB, its photochemistry becomes very similar. Fluorine substituents at the central benzene ring are shown to have only small effects on the optical properties of BPEB.
Gesehen am 22.07.2020